History, methodology and identity for a 21st century social economics - Dolfsma, Wilfred; Hands, D. Wade; McMaster, Robert (Political economist) (Abingdon, Oxon ; NewYork, NY : Routledge, 2019)
This book seeks to advance social economic analysis, economic methodology, and the history of economic thought in the context of twenty-first-century scholarship and socio-economic concerns. Bringing together carefully selected chapters by leading scholars it examines the central contributions that John Davis has made to various areas of scholarship. In recent decades, criticisms of mainstream economics have rekindled interest in a number of areas of scholarly inquiry that were frequently ignored by mainstream economic theory and practice during the second half of the twentieth century, including social economics, economic methodology and history of economic thought. This book contributes to a growing literature on the revival of these areas of scholarship and highlights the pivotal role that John Davis's work has played in the ongoing revival. Together, the international panel of contributors show how Davis's insights in complexity theory, identity, and stratification are key to understanding a reconfigured economic methodology. They also reveal that Davis's willingness to draw from multiple academic disciplines gives us a platform for interrogating mainstream economics and provides the basis for a humane yet scientific alternative. This unique volume will be essential reading for advanced students and researchers across social economics, history of economic thought, economic methodology, political economy and philosophy of social science.
OCLC-licensed vendor bibliographic record.
Keywords: Davis, John Bryan; Economics -- Philosophy; Economics -- History -- 21st century; Economic development -- Social aspects; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Economics / Theory